Problematic Character Learning During Covid-19 Pandemic in Primary School of Banyumas District - Subur Subur (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study analyses the various character learning difficulties experienced by primary school (SD) teachers and students in online learning during the Covid-19 pandemic and its effects. The unexpected spread of the Covid-19 outbreak has caused many problems in a learning activity in primary school, especially in character material. The data sources of this study are the teacher of primary schools in the suburban area of Banyumas and stakeholders in the character learning process. This study uses a descriptive method with a qualitative research approach. Techniques of data collection are in-depth interviews and observation. Data analysis is with reduction, display, and conclusion. The results showed that the problematic character learning through online learning during a pandemic includes the low intensity of interaction between teacher and students as a result, difficulty in the interaction between teachers and students even misunderstandings often arise, the delivering character material need explanation and concrete example, the inadequate response and understanding of students to character material, the difficulty of teacher in monitoring changes in student's behavior, the difficulty of parents in assisting students, the difficulty of teacher in assessing UTS (midterm) or UAS (final examination) subject to a character. Even if it is minimal, a solution that can be done is to send video and voice chat that contain messages of moral values for children